Immune Response and its Effects on the Host during Helminthic Infections - Gazi, Umut; Taylan Özkan, Ayşegül (European Journal of Therapeutics, 2023)
Helminths are multicellular organisms causing chronic infections affecting nearly one-third of the global population. They are experts at immunomodulation, and pathologic outcomes are generally observed in patients with immunodeficiencies or with exaggerated levels of anti-helminth immune responses. Elimination of helminths is usually mediated by T-helper type-2 (Th2) immune responses, characterized by the induction of Immunoglobulin E (IgE) release, increase in eosinophil and mast cell levels, and elevation in the production levels of Th2 cytokines. However, the triggered mechanisms may also depend on the location of the parasite. This is because tissue invasion, an immune evasion strategy for parasites, was considered to activate more Thelper type 1 (Th1) cells in tissues. During chronic infections, immune response regulatory pathways become more influential, thereby reducing the levels of the peripheral T-cell-mediated responses against parasitic antigens. The resultant immune response is termed as “modified Th2 response” and is characterized by enhanced levels of anti-inflammatory cytokine production and regulatory immune cells as well as high IgG4/IgE ratios. Immunomodulation during chronic helminth infection is not limited to only parasite-specific responses. It can influence the efficiency of vaccination, host susceptibility to infections, and allergen or autoantigen responses. This review discusses anti-helminth immune responses. Moreover, it highlights current literature on the effects of chronic helminth infections on host health as well as their possible use as a treatment strategy against autoimmune, autoinflammatory, and allergic diseases.